2004
DOI: 10.1002/prot.10581
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal disulfide bridge conformers by experimental methods and by ab initio and DFT molecular computations

Abstract: A systematic comparison is made between experimental and computational data gained on vicinal disulfide bridges in proteins and peptides. Structural and stability data of ab initio and density functional theory (DFT) calculations on the model compound 4,5-ditiaheptano-7-lactam and the model peptide HCO-ox-[Cys-Cys]-NH2 at RHF/3-21G*, B3LYP/6-31+G(d), and B3LYP/6-311++G(d,p) levels of theory are presented. The data on Xxx-Cys-Cys-Yyy type amino acid sequence units retrieved from PDB SELECT, along with data on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 59 publications
3
43
0
Order By: Relevance
“…Previous conformational analysis of oxidized CC rings in peptides has suggested conformations with a cis-amide (11,29). In contrast, analysis of CC motifs in the PDB concluded that the occurrence of the cis conformation was remarkably low (30). Hence, although the cis structures have 77 Se chemical shifts in the region of interest, they may not have contributed to the observed spectra.…”
Section: Density Functional Theory Conformation Search and Gauge-invamentioning
confidence: 88%
“…Previous conformational analysis of oxidized CC rings in peptides has suggested conformations with a cis-amide (11,29). In contrast, analysis of CC motifs in the PDB concluded that the occurrence of the cis conformation was remarkably low (30). Hence, although the cis structures have 77 Se chemical shifts in the region of interest, they may not have contributed to the observed spectra.…”
Section: Density Functional Theory Conformation Search and Gauge-invamentioning
confidence: 88%
“…The cis and trans isomers of a model peptide of the form CH 3 CO-[CysCys]-NH 2 with the S-S disulfide torsional angles of Ϯ90 were constructed using the GausView molecule building tools. The geometric parameters for these starting structures were derived from the lowest energy conformers from previous ab initio calculations on a similar model peptide (21). Energy minimizations were performed on the four starting structures of the model peptide.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, many workers have speculated on a role in receptor gating involving cis-trans isomerization of the amide and/or gauche(ϩ)/gauche(Ϫ) interconversion of the disulfide (10,18,19,21,22). Conventional mutagenesis studies are expected to produce severely impaired receptors, and so it has been challenging to design unambiguous probes of disulfide function.…”
Section: Nicotinic Acetylcholine Receptors (Nachrs)mentioning
confidence: 99%
“…[42][43][44] The disulfide bond between two adjacent cysteine residues (i.e., a vicinal disulfide bond) is referred to in the literature as a "forbidden" disulfide, involving an eightmembered ring structure in which the peptide bond typically adopts a highly distorted, non-planar trans conformation. [43][44][45][46] Vicinal disulfides have been reported, for example, in insecticidal atracotoxins, 47 the Helicobacter pylori heat shock protein A 48 and the human replication protein A (RPA). 49 The formation of a vicinal disulfide bond in RPA alters the direction of the backbone and causes a strain in the peptide chain.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide bond in the eight-memberd ring of the vicinal Cys29-Cys30 adopts a clearly distorted trans-conformation (w 5 103.28), consistent with the other reported vicinal disulfide bonds. 45,46 Therefore, the zinc center in SAP30L forms a redox switch, which, upon oxidative stress, releases the coordinated zinc ion with a concomitant formation of the two specific disulfide bonds, a vicinal Cys29-Cys30 and Cys38-Cys74 (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%